What Lies Beneath Baby Shark Song?: A Critical Analysis On Korean Society - Arif, Muhammad; Triyono, Sulis (Master Program in Linguistics, Diponegoro University, 2017)
This study aims to analyze a phenomenal song entitled â€œBaby Sharkâ€ composed by the Pinkfong, a South Korean media startup. The song has become viral over children and adults alike. This research is undertaken to find out; the composerâ€™s attitudes, the social relation among the participants, and the context of the situation in the discourse. The object of the study is obtained from the whole lyrics. Then it is analyzed through Appraisals and Critical Discourse Analysis by connecting every single line to the intentional marketing and social context. Finally, the conclusion shows that â€œBaby Sharkâ€ is a song about local wisdom education in Korea. The composer implicitly admires the shark and uses it as metaphor of Korean people mindset. The composer intends to give his full support and persuades the listener about hard working culture in Korea